Prognostic implication of left ventricular hypertrophy regression after antihypertensive therapy in patients with hypertension - Kim, Hyue Mee; Hwang, In-Chang; Choi, Hong-Mi; Yoon, Yeonyee Elizabeth; Cho, Goo-Yeong (Frontiers in Cardiovascular Medicine, 2022)
Background Left ventricular (LV) hypertrophy (LVH) in patients with hypertension is a significant risk factor for cardiovascular mortality and morbidity. However, the prognostic implication of LVH regression after antihypertensive therapy has not been clearly investigated. Methods Patients who underwent echocardiography at the time of the diagnosis of hypertension and repeated echocardiography at an interval of 6–18 months were retrospectively identified. LVH was defined as LV mass index (LVMI) >115 g/m2 (men) and >95 g/m2 (women). LVH regression was defined as LVH at initial echocardiography with normal geometry or concentric LV remodeling at follow-up echocardiography. Cardiovascular mortality, hospitalization for heart failure (HHF), coronary revascularization, stroke, and aortic events were analyzed according to changes in LVMI and geometry. Results Of 1,872 patients, 44.7% (n = 837) had LVH at the time of diagnosis; among these, 30.7% showed LVH regression. The reduction in LVMI was associated with the reduction in BP, especially in those with LVH at baseline. During follow up (median, 50.4 months; interquartile range, 24.9–103.2 months), 68 patients died of cardiovascular causes, 127 had HHF, and 162 had vascular events (coronary revascularization, stroke, and aortic events). Persistent or newly developed LVH during antihypertensive therapy was a significant predictor of cardiovascular mortality and events, especially HHF. On multivariable analysis, women, diabetes, atrial fibrillation, coronary artery disease, larger LVMI and end-diastolic dimension, and less reduction in systolic BP were associated with persistent or newly developed LVH. Conclusion LVH regression in patients with hypertension is associated with a reduction in cardiovascular events and can be used as a prognostic marker.